1977
DOI: 10.1126/science.897668
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Autoantibodies in Vasectomized Rats of Different Inbred Strains

Abstract: An immune response to antigens of spermatozoa occurs after vasectomy in rats of some inbred strains, but not in others. Antibodies to rat spermatozoa were detected by indirect immunofluorescence in some of the serums of vasectomized rats of the following strains: 80 percent of Lewis, 47 percent of Brown Norway, 13 percent of Buffalo, 12 percent of Wistar-Furth, and 11 percent of ACI rats. No such antibodies were detected in the serums of vasectomized Fischer, Dark Agouti, and Sprague-Dawley rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…These studies were confined to outbred rats, primarily to those of the Sprague-Dawley strain. It has been shown that an immune response to sperm antigens occurs after vasectomy in some rat strains but not in others (Bigazzi, Kosuda & Harnick, 1977). Bigazzi et al (1977) were unable to detect sperm autoantibodies in vasectomized rats of the Sprague-Dawley strain but did find such antibodies in 80 % of inbred rats belonging to the Lewis strain.…”
Section: Introductionmentioning
confidence: 96%
“…These studies were confined to outbred rats, primarily to those of the Sprague-Dawley strain. It has been shown that an immune response to sperm antigens occurs after vasectomy in some rat strains but not in others (Bigazzi, Kosuda & Harnick, 1977). Bigazzi et al (1977) were unable to detect sperm autoantibodies in vasectomized rats of the Sprague-Dawley strain but did find such antibodies in 80 % of inbred rats belonging to the Lewis strain.…”
Section: Introductionmentioning
confidence: 96%
“…The low titer of sperm-agglutinating antibodies detected only after 8 months in the sham-operated and untreated rats could be attributed to aging. The difference between the titers obtained in this experiment and those obtained by Rumke and Titus [ l l ] may be explained on the basis of differences in the immune response among different strains of rats [3].…”
Section: Discussionmentioning
confidence: 62%
“…Humoral immunity to spermatozoan antigens after vasectomy is well documented in man and laboratory animals (Rumke & Titus, 1970;Shulman et al, 1972;Samuel et al, 1975;Bigazzi et al, 1977). Morphological changes, consistent with this humoral response, have been described in the first regional testicular lymph node of rats after left unilateral vasectomy (McDonald & Scothorne, 1986,1989.…”
Section: Introductionmentioning
confidence: 83%